The Correlation of Characteristics of Type 2 Diabetes Mellitus Patients and Medication Adherence Level: A Case Study in Community Pharmacy - Rawitr, Kiki; K, Khairunnisa; W, Wiryanto (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: Patients with diabetes mellitus (DM) are patients with a low level of medication adherence. Low adherence causes poor glycemic control, thus increasing the risk of various chronic complications (microvascular and macrovascular). Objective: This study aims to determine the correlation between patient characteristics including gender, age, education level, occupation, duration of illness, and comorbidities on medication adherence to type 2 diabetes mellitus patients at the pharmacy. Methods: This study used an observational method with a cross-sectional study design. The study involved 40 DM type 2 patients who met the inclusion criteria at one of the pharmacies in Medan in August-September 2020. Data on the level of treatment adherence were obtained using the MMAS-8 questionnaire (Morisky Medication Adherence Scale-8). Data were analyzed using the Chi-Square statistical test. Results: The results showed that the majority of patients involved in this study were women (57.5%), aged 45-65 years (92.5%), high school education level (47.5%), and private employees/ traders/ labor (45%). This study also showed that the majority of patients had a low level of adherence (55%), duration of suffering from type 2 diabetes, 1-5 years (18%), and with comorbidities (75%). The relationship between patient characteristics and adherence level was gender (p = 0.636); age (p=0.922); education level (p=0.275); work (p=0.241); duration of illness (p=0.629); and with comorbidities (p=0.752) the level of treatment adherence was not significant (p>0.05). Conclusion: Based on the results of the study it was concluded that there was no significant relationship between patient characteristics including gender, age, level of education, occupation, duration of disease, and comorbid diseases on the level of medication adherence of type 2 DM patients at the community pharmacy.